2020
DOI: 10.5937/tehnika2003343t
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the logistics system development scenarios: Case study of the trading company

Abstract: The paper presents the procedure for selecting a scenario for the development of the logistics system in a company with a developed trading and logistics network, but also with the significant supply problems. In order to solve the existing logistics problems, but also to respond to future requirements and business plans, four logistics system development scenarios are defined. Each scenario has certain characteristics which can be seen as the advantages or disadvantages in the comparative analysis. Since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This enabled the sustainability evaluation of concept variants through a set of qualitative and quantitative criteria. The selected criteria are not novel and are adopted from the existing scientific literature [12,64,65]. This proved the second research hypothesis, which stated that it is possible to develop a robust methodology for planning such concepts by considering all relevant tactical and operational level planning questions and qualitative and quantitative criteria in evaluating different concept variants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This enabled the sustainability evaluation of concept variants through a set of qualitative and quantitative criteria. The selected criteria are not novel and are adopted from the existing scientific literature [12,64,65]. This proved the second research hypothesis, which stated that it is possible to develop a robust methodology for planning such concepts by considering all relevant tactical and operational level planning questions and qualitative and quantitative criteria in evaluating different concept variants.…”
Section: Discussionmentioning
confidence: 98%
“…According to the existing literature that performed the prioritization of criteria before solving city logistics-related problems [12,64,65], the following criteria weights are adopted: w 1 = 0.161, w 2 = 0.116, w 3 = 0.202, w 4 = 0.243, w 5 = 0.151, w 6 = 0.127. Articles [12,64,65] performed the criteria evaluation according to the opinions and goals of stakeholders in Belgrade (and Serbia in general); therefore, they could be considered relevant for this study as well. The adopted criteria weights compose the initial concept variants evaluation scenario (Sc.…”
Section: Case Study and The Application Of The Developed Methodologymentioning
confidence: 99%
“…In study by Amin et al [14], the AHP-TOPSIS model was used to set the best pallet placement in storage racks. Besides, a lot number of research have been performed in the field of transport, such as study by Yannis et al [15] concluding that MCDM models are applied mainly to evaluate transport options rather than transport policies or projects, with conclusion that most commonly applied method in transport sector is the AHP [16,17]. Based to study by Mardani et al [18] where different papers were analyzed, it was concluded that, within transport, ranking the quality of service was the first area of using of MCDM.…”
Section: Short Literature Reviewmentioning
confidence: 99%